2023
DOI: 10.15537/smj.2023.44.2.20220680
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the adverse effects of COVID-19 vaccine in different scenarios in Saudi Arabia

Abstract: Objectives: To assess the different side effects of COVID-19 vaccines at different scenarios in Saudi Arabia. Methods:This cross-sectional study sought to investigate the side effects of COVID-19 vaccines through an online survey of 2,718 participants in Saudi Arabia.Results: People can manage their expectations about vaccine side effects and deal with symptoms better by knowing beforehand that they are likely to experience mild side effects for a short period, symptoms that are manifested regardless of age, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Conversely, Covaxin recipients reported a higher incidence of soreness at the injection site, indicating potential differences in local reactogenicity. These findings align with previous research demonstrating differences in the side-effect profiles among COVID-19 vaccines [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Conversely, Covaxin recipients reported a higher incidence of soreness at the injection site, indicating potential differences in local reactogenicity. These findings align with previous research demonstrating differences in the side-effect profiles among COVID-19 vaccines [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…The necessity of this study is further supported by a growing body of literature emphasizing the importance of understanding vaccine-specific side effects to inform public health strategies. Previous studies have demonstrated variations in reactogenicity and immunogenicity among different COVID-19 vaccines, highlighting the need for comprehensive evaluations to guide vaccine administration [ 9 , 10 , 12 , 13 ]. By comparing Covishield and Covaxin, this study contributes to the existing knowledge base and provides actionable insights for healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%